Faktor-faktor yang mempengaruhi audit report lag - FRISKA FIRNANTI (Jurnal Bisnis dan Akuntansi, 2016)
The purpose of this study is to test and to analyze the effect of firm size, solvency, auditor reputation, firm performance, liquidity, and firm age to audit report lag, of manufacturing firm that listed at Indonesian Stock Exchange in the period of 2010-2013. The method used is multiple regression analysis using SPSS. The result show solvency has a significant positive effect to firm’s audit report lag. Auditor reputation and firm performance have a significant negative effect to firm’s audit report lag. Thus, investor and company may consider these factors in making decisions that related to audit report lag. Company can also improve their performance so that the factors that are considered to effect audit report lag can be reduced to perform better timeliness of financial statement presentation.